Floodport : An Interactive Coastal Flood Risk Training App - Nisiforou, Olympia A.; Alamanos, Angelos; Nagkoulis, Nikolaos; Koundouri, Phoebe (My University, 2025)
Coastal flooding is driven by multiple interacting hazards such as tides, storm surges, heavy rainfall, and sea-level rise. Its complex nature makes it challenging for learners to fully grasp. Interactive learning through technology-enhanced tools offers new opportunities for improving comprehension and engagement. We present the FloodPort, an interactive educational application designed to simulate coastal flood scenarios at a port. Students act as coastal risk analysts, adjusting key parameters such as high tides, storm surge, rainfall runoff, sea-level rise, and the height of engineering structures like the port dock. These drivers can act independently or in combination. The user can explore build-in climate change scenarios or develop its own custom scenario, exploring thus complex hazard interactions and design safer port configurations. Initially developed in Excel and Python, the app has been transformed into a freely accessible Shiny App format (using R), supporting active learning and scenario-based exploration in the classroom.
Keywords: Climate change; Civil Engineering; Coastal Floods; Interactive learning; Ports